Prevalence of Plasmodium Falciparum and Plasmodium Vivax in Choti Zareen, Dera Ghazi Khan, Pakistan - TABISH, SABA; ZAHEER, NAIREEN; SAHAR, AKASH; ABBAS, MUSTANSAR; SAGHIR, RUBAB; BATOOL, FAREEHA; IFTIKHAR, MUHAMMAD MADNI; KAMAL, MUHAMMAD; QADEER, IQRA; KHAN, GUL ZAHRA (Pakistan Journal of Medical & Health Sciences, 2025)
Plasmodium is and endoparasite of human, which belongs to class apicomplexan of Protista. There are many species of this parasite, but here we study about two, which are majorly occurring in Pakistan. Our research area for study was Choti Zareen, D.G Khan, Pakistan. We study the different groups of peoples on the bases of Sex/ Gender, Age, Education, and Socio-economicstatus. The ratio of malarial disease was higher in females than males, in early age children’s and aged peoples than juvenile, in uneducated than educated peoples and in socio-economic peoples and poverty’s ones. The analysis was done by statistical software, and comparison of results have been done through graphical representations.